Cerebral Palsy - Miller, Freeman; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2005)
Cerebral palsy is a lifelong condition that affects the individual, family, and immediate community. Therefore, the goal of allowing the individual with cerebral palsy to live life with the least impact of the disability requires c- plex attention to the individual and the family. Furthermore, society needs to be sensitive and to accommodate individuals with disabilities by limiting architectural impediments and providing accessible public transportation and communication. The educational system provides the key means for helping the individual prepare to function in society to his or her maximum ability. In many ways, the medical care system probably has the least sign- icant role in preparing the child with cerebral palsy to function optimally in society. However, the medical care system is the place where parents first learn that their child has developmental issues outside the expected norm. It is almost universally the place where parents also expect the child to be made normal in our modern society. In earlier times, the parents would expect healing to possibly come from the doctor, but also they would place hope for healing in religion. As this belief in spiritual or miraculous healing has - creased, a significant font of hope has decreased for parents of young ch- dren with disabilities.
Cerebral Palsy Management -- The Child, the Parent, and the Goal -- Etiology, Epidemiology, Pathology, and Diagnosis -- Patient Management -- Neurologic Control of the Musculoskeletal System -- Therapy, Education, and Other Treatment Modalities -- Durable Medical Equipment -- Gait -- Upper Extremity -- Spine -- Hip -- Knee, Leg, and Foot -- Rehabilitation Techniques -- Neurodevelopmental Therapy -- Strengthening Exercises -- Balance Interventions -- Electrical Stimulation Techniques -- Hippotherapy -- Aquatic Therapy -- Assistive Devices -- Seating Systems -- M.O.V.E.? (Mobility Opportunities Via Education) Curriculum -- Occupational Therapy Extremity Evaluation -- Intrathecal Baclofen Pumps -- References -- Surgical Techniques -- Upper Extremity Procedures -- Spinal Procedures -- Hip Procedures -- Knee Operative Procedures -- Foot and Ankle Procedures.
Keywords: Orthopedics; Pediatrics; Rehabilitation; Rehabilitation medicine; Orthopedics; Conservative Orthopedics; Surgical Orthopedics; Pediatrics; Rehabilitation; Rehabilitation Medicine